Meta-Analysis Study for the Use of Project Based Learning Models in Teaching and Learning Activities - Dodik Widarbowo; Nofirman Nofirman; Jasiah Jasiah; Miftahus Surur; Enny Diah Astuti (Journal on Education, 2023)
This study aims to analyze the effectiveness of using the project-based learning (PjBL) learning model on students' biology learning outcomes. The method used is meta-analysis, a method for synthesizing research results from various studies using statistics commonly used in primary studies. The research instrument is in the form of a coding sheet that contains the necessary data and journal information. The research findings show that overall, the PjBL learning model is effective for biology learning, with a large effect size of 1.050 and a very high effect category. The PjBL model also provides influence and is effective in terms of area, educational level, and its application in biology learning to improve learning outcomes, creative thinking skills, critical thinking skills, and in larger groups, namely 21st century skills and knowledge or cognitive learners.